Challenges in Developing English Speaking and Listening Skills via Zoom - Ahmad Syafiq Aqil Nazili; Rizka Indah Aiyrum Aiyrum (Universitas Muhammadiyah Lampung, 2023)
The COVID-19 pandemic has expedited the transition to online learning, particularly within English education that necessitates active oral engagement. The Zoom platform is predominantly employed for live instruction; however, its efficacy in enhancing Speaking and Listening skills has not been extensively examined. This study investigates students' experiences concerning challenges related to these skills during Zoom-based English classes. Employing a qualitative, descriptive phenomenological methodology, the research involves fifteen students from the Law Study Program at UIN Syarif Hidayatullah Jakarta, selected through purposive sampling. Data collection was carried out through in-depth interviews and analysed using Thematic Analysis. The findings reveal three primary categories of challenges: technical, psychological, and pedagogical. Technical challenges encompass poor audio quality, unstable internet connections, and communication delays, which impede listening comprehension and diminish speaking confidence. Psychological barriers include anxiety and Zoom fatigue, which affect concentration, motivation, and participation. Pedagogically, Zoom renders oral interactions unnatural, breakout rooms are less effective, and lecturer feedback is limited- all of which constrain the development of oral skills. Overall, the enhancement of Speaking and Listening proficiency via Zoom hinges on technological readiness, students' emotional states, and instructional strategies. An adaptable, engaging, and student-centred approach is essential to improve oral learning efficacy within a virtual context.